State-Owned Enterprises as Countercyclical Instruments : Experimental Evidence from the Infrastructure Sector - Herrera Dappe, Matias; Musacchio, Aldo; Pan, Carolina; Semikolenova, Yadviga; Turkgulu, Burak; Barboza, Jonathan (World Bank, Washington, DC, 2022)
This paper examines the effects of a negative macroeconomic shock on the financial performance of state-owned enterprises (SOEs) in infrastructure. It exploits the differential effects of a drastic fall in oil prices (in 2014–15) on SOEs in energy-rich countries relative to SOEs in non-energy-rich countries, matching firms based on their fuel expense ratio. The results—based on a balanced sample using coarsened exact matching and a differences-in-differences estimation—indicate that fully owned SOEs (FSOEs) that suffered a negative macroeconomic shock performed worse than those that did not. FSOEs that suffered a shock also received large fiscal transfers from the government to cope with the shock for three years after the shock. Despite the transfers, they reduced their capital expenditures as a consequence of the shock.